What is 5c plus 7c plus 2b?
12c + 2b
1 person found this useful
ab - 2b + ac -2c. = b(a - 2) + ac - 2c. = b(a - 2) + c(a - 2). = (b+c)(a - 2)
-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b
Yes, on a pyramid with a square base. Remember that the b2 is b squared.
2B + 3 = 18 B = 7.5 18 - 3 = 15 2 /15 = 7.5 If the answer is "18", you need to take the "3" away that you have added. After taking the "3" away, it will be easier to figure out what "B" equals. Now, because you have taken away the "3", you are left with "2B". "2B", meaning "2 x B", just means you …need to do the opposite to figure out the answer, therefore being "2 / B". Because you took the "3" and you had "15" left over, you will just have to half that, therefore "B" equals "7.5". (MORE)
3a + 2b is an expression in algebra. If you make 3a + 2b equal to something then you can find the values of "a" and "b" Lets say you make 3a + 2b equal to 23 3a + 2b = 23 Now find "a" and "b" to make this equation true... 3(5) + 2(4) = 23 15 + 8 = 23 23 = 23 Correct So in this case a=5 and b=4
8b + 11 - 3b = 2b + 2 . 5b + 11 = 2b + 2 . 5b - 2b = 2 - 11 . 3b = -9 . b = -3
Amazing! Exactly the same question was posted here on WikiAnswers last September 23. What an incredible coincidence! 8b + 11 - 3b = 2b + 2 That 8b on the left side can be combined with the -3b to make 5b . 5b + 11 = 2b + 2 Subtract 2b from each side: 3b + 11 = 2 Subtract 1…1 from each side: 3b = -9 Divide each side by 3: b = -3 (That's the same answer they got last September.) (MORE)
Presumably this is an equation in the form of: b+2b-11 = 88 3b = 88+11 3b = 99 b = 33 However, if this was b exponent 2 (squared) or b^2 for the first b,then it is a quadratic expression. b^2 + 2b - 11 = 88 b^2 + 2b - 99 = 0 (b+11)(b-9) = 0 B = -11 or 9
3c - 12 = 14 + 5c Subtract 3c from each side: -12 = 14 + 2c Subtract 14 from each side: -26 = 2c Divide each side by 2: -13 = c
-3.5. 2c would turn into -1.5 and seven wold turn to 3.5. add the two together and you get 2. 2+6=8 and you have your answer.
a + b - 2 is the answer in simplest terms. without telling us what a or b is this is the most accurate answer.
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
3ab + 3ac + 2b 2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)
All the terms in b add to 11, so 11b = 132 making b = 12
Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).
5b - 3 - 2b = 6b - 3 3b - 3 = 6b - 3 3b - 6b = 3 - 3 b = 0
A = 2b + c Subtract 'c' from each side: A - c = 2b Divide each side by 2: b = 1/2 (A - c)
4a+2b-1a+9b combine all alike variables using commutative property of addition 4a-1a+2b+9b Then add the like variables 3a+11b
-4c charge can make the exerted force go on another object such as the 5c positive charge. because wen u multiply em' they make a similarity between them such as -4c+5c which equals to -c or -1c (same thing):)
5c + 15= 30 - 15 -15 5c = 15 If your solving for just c..... 5c/5 = 30/5 c= 3 Hope this helps adding further your question is incomplete you must ask for thevalue of C, since its a arithmetic equation.
2b-8=-b+7 3b-8=7 Add 'b' to both sides, eliminating the variable on the right side 3b=15 Add 8 to both sides to isolate the number on one side b=5 divide each side to eliminate the coefficient on b. The answer is b=5.
The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b
3c - 12 + 5c = 12 Combine the 'c' terms on the left side: 8c - 12 = 12 Add 12 to each side: 8c = 24 Divide each side by 8: c = 3
4c 2 + 5c + 2c = 4c 2 + 7c = c(4c + 7)
You can't tell a thing about -5c+9 until you know what 'c' is. And every time 'c' changes, -5c+9 changes.
The equation (b 2 - 2b) + (3b - 6) = b 2 + b - 6
3a=3xa and if a = 5 it would be 3x5 which = 15 2b=2xb and if b = 2 it would be 2x2 which = 4 15+4=19
To factor this equation... if you have learned before, find 2 numbers that add up to the middle value (-7) and multiply together to have a product of the last value (+10). You can use guess and check for this problem... but if you haven't already found it... the sum of -5 and -2 is -7... and the pr…oduct of -5 and -2 is +10, so we can use the values -5 and -2.... The solution is (c-5)(c-2) = c^2 - 7c + 10. (MORE)
Collecting like terms together, 10c = 240, therefore, c = 240/10 c is therefore equal to 24.
5b - 7 = 2b +5 5b-2b-7=2b -2b +5 subtract 2b from each side to get b on one side 3b-7=5 3b-7+7 = 5+7 now add 7 to both sides to get the numbers on one side 3b = 12 3b/3 = 12/3 finally divide both sides by 3 to solve for b b = 4
NO,because in quadratic equation highest power of a variable is 2. e.x. 4x 2 -20x+10=0.
Put the bs on the same side of equal sign then put the other numbers on the different side getting 3b=-4 then u divide by 3 to get b=-4/3
20c + 5 = 5c + 65 Divide through by 5: 4c + 1 = c + 13 Subtract c from both sides: 3c + 1 = 13 Subtract 1 from both sides: 3c = 12 Divide both sides by 3: c = 4 20c + 5 = 5c +65 20c - 5c= 65 - 5. 15c = 60. 15c/15 = 60/15. c = 4 (alternative method).
It equals 10c+2 because you have to combine like terms when you use variables. So since there is a 7c and a 3c you add those because it says plus add you end up with 10c+2 because you are still adding the 2.
2B Multiplied by 3 plus B = 7B. Here is how it's worked out. You start with 2B, multiply that by 3 and you get 6B. Now all you have to do is add the last B, therefore adding 1B to equal 7B.
The value of b is 44.5 * * * * * Missed the 2! b + 2b - 1 = 88 Combining like terms: 3b - 1 = 88 Add 1 to both sides: 3b = 89 Divide both sides by 3: b = 89/3 = 29 2 / 3
You need values for a and b, then you multiply a by 3, b by 2 and add your answers.
4a + 3c - 2b - c + a - b = 5a - 3b + 2c
It isn't always. In fact, it almost never is. The only time it is is when 'b' is 2 2 / 3 .
5c+7=23 -7 -7 5c=16 /5 /5 c= 3 & 1/5 or 16/5 thats really easy algebra 1 homework isn't it
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals". There is no visible symbol between " ... eq…uals 4" and "2b plus 1". (MORE)
It is a linear expression with one variable, b. Since it is not an equation it cannot be solved.
5 and 7 are two coefficient. And that is all. There is no third coefficient.
It is a single equation of direct proportionality. It cannot be solved since that would require two linear equations.
That will depend on the plus or minus value of 10 or maybe there is a missing equality sign.
If you mean 3+4b=7-2b, then you would start out with that equation I just listed. Then, you would add 2b to both sides, taking you to 3+6b=7. Then, you would subtract 3 from both sides, taking you to 6b=4. Lastly, you would divide both sides by 6, taking you to b=4/6, or 2/3. (Two-thirds) Keep in m…ind that when you divide or subtract a number from both sides, the side in which it was on (ex. 4b=8), loses that number (4) and only affects THAT number. That is, on the side in which it was ON. Then, when you divide, it affects the other side of the equation in the same way, but this time affecting any and ALL numbers and variables. In this case, the ex. would turn out to be b=2. But if it had originally been 4b=8+b, then it would turn out to be b= 2+(b/4). (MORE)
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".
Placing a question mark at the end of a list of expressions or numbers does not make it a sensible question. There is insufficient information for us to even begin to understand this question. Please edit the question to include more context or relevant information.
That may be, but a single linear equation in three unknown variables cannot be solved.
If this was b exponent 2 (squared) or b^2 for the first b, then itis a quadratic expression. b^2 + 2b - 11 = 88 b^2 + 2b - 99 = 0 (b+11)(b-9) = 0 B = -11 or 9